The World We Live In - Brush, Katharine; Manson, Gary; Washington Office of the State Superintendent of Public Instruction, Olympia (Philadelphia : The Blakiston Com, 1944)
This publication presents guidelines to aid curriculum committees in the construction of elementary and secondary social studies programs which take account of the most current thinking. Fifteen guidelines, based on the components of knowledge, thinking, and social action, deal with purposes, content, and instructional strategies. Each guideline is accompanied by a discussion of its meaning and why it is needed, and two to four well-selected bibliographic items. Introductory and concluding pages present the background and rationale of the publication, suggestions for its use, and a glossary of key terms. The booklet is generously illustrated with attractive photographs which suggest the vitality of issues with which a good social studies program deals. (IM)
Microfiche.
Keywords: Affective Objectives; Behavioral Objectives; Citizenship; Cognitive Objectives; Curriculum Development; Curriculum Evaluation; Curriculum Guides; Elementary Education; Relevance (Education); Secondary Education; Social Action; Social Problems; Social Sciences; Social Studies